STUDENTSGRAPHIC INCREASING LITERACY INNOVATION-CREATIVITY AND IMAGINATIONOF THE WORLD, TO THE FORMATION - Kamalov Azamat Farkhodovich (Galaxy International Interdisciplinary Research Journal, 2023)
Today, technology in every aspects of our life, in particular, education, production or active also entered our daily life. Of course, this is how we live, we work and most importantly to give an education, or even significantly effect. Information technology, other wireless devices are increasing the demand for mobile tools and the fact that this requires the introduction of modern technology in our country and also on the basis of effective schools. This process, students willpush the development of knowledge in the world, the master obviously earned place is incomparable.